The arbitrage pricing theory : a study on the risk- return relationship in the Kuala Lumpur stock exchange / Mohd Lokman Mohd Kassim - Mohd Kassim, Mohd Lokman (1994)
This research examines the significance of the risk factors in influencing the returns on investment in the Kuala Lumpur Stock Exchange (KLSE). The returns on investment are reflected by the quarterly variations in the Composite Index (CI) of the Kuala Lumpur Stock Exchange and the risk factors are the quarterly changes in the economic indicators from March 1989 to December 1993. The CI has been selected to represent a portfolio of 86 securities of the KLSE and the Multiple Regression Analysis has been employed to determine the factors' betas and risk premiums to be applied for the Arbitrage Pricing Theory model. The results of the study suggested that the selected economic indicators are not statistically significance in influencing the returns on investment in the KLSE. Therefore, they indicate that there are other significant factors in influencing the returns on investment in the KLSE. However, they show that the real Gross Domestic Product and the money supply have a positive relationship with the returns while the Consumer Price Index together with the Average Lending Rate have an inverse relationship with the returns on investment in the KLSE.